Manganese ferrite decorated N-doped polyacrylonitrile-based carbon nanofiber for the enhanced capacitive deionization. (1st January 2022) - Nguyen, Thi Kim Anh; Kuncoro, Eko Prasetyo; Doong, Ruey-An
Highlights: The 1-D MnFe2 O4 /N-ACF hybrid for high-performance capacitive deionization (CDI) is developed. The meso-macroporous structures of MnFe2 O4 /N-ACF accelerate the ion transfer rate. The CDI performance of MnFe2 O4 /N-ACF is a function of flow rate, salt concentration, and voltage. MnFe2 O4 /N-ACF exhibits a high SEC of 41.2 mg g −1 and superior cyclability for 50 cycles. Abstract: In this study, the manganese ferrite was decorated onto 1-dimensional based activated carbon fiber (MnFe2 O4 /N-ACF) by precipitation method for capacitive deionization (CDI) application. Polyacrylonitrile (PAN) and 2-methylimidazole (2MI) were used as the carbon precursor and nitrogen dopant for the fabrication of 200 nm N-doped ACF (N-ACF). After the deposition of 5–15 wt% MnFe2 O4 nanoparticles, the diameter of MnFe2 O4 /N-ACF increases to 300–400 nm, and the addition of 10 wt% MnFe2 O4 can well deposits onto the surface of N-ACF to decrease the impedance to accelerate the electron transfer as well as to enhance the specific capacitance up to 422 F g −1 at 5 mV s −1 . Furthermore, the CDI Ragone plots indicate that the specific electrosorption capacity (SEC) of NaCl by 10 wt% MnFe2 O4 /N-ACF is in the range of 23.4–41.2 mg g −1, which is a function of applied voltage, NaCl concentration, and flow rate. A SEC of 41.2 mg g −1 in the presence of 500 mg L −1 can be achieved when the flow rate and applied voltage are 10 mL min −1 and 1.4 V, respectively. Moreover, the as-prepared electrode materials can be recycled for at least 50 cycles and the SEC can be maintained over 93% of the original activity after 50 cycles, indicating the excellent cycling stability of MnFe2 O4 /N-ACF electrode. Results obtained in this study signify that the 1-D MnFe2 O4 /N-ACF is a promising CDI electrode material, which can provide a productive solution for elevating the platform with low cost and high efficiency for CDI technology. Graphic abstract: Image, graphical abstract